On String Graph Limits and the Structure of a Typical String Graph - Janson, Svante; Uzzell, Andrew J. (Journal of graph theory, 2017)
We study limits of convergent sequences of string graphs, that is graphs with an intersection representation consisting of curves in the plane. We use these results to study the limiting behavior of a sequence of random string graphs. We also prove similar results for several related graph classes.